EXPLORING THE IMPACTS OF POST-COVID-19 ON REMOTE WORK FOR WORKING FROM HOME EFFECTIVENESS - Kismono, Gugup; Danarilia, Vania Olivine; Araminta, Devina (ULTIMA Management, 2024)
Abstract-This research investigates the multifaceted dynamics of remote work during the COVID-19 pandemic. It focuses on the interplay between role conflict, environmental constraints, resource constraints, acceptance of the way of working, and mental health in determining its effectiveness. This study integrates them heavily to understand how role conflict, environmental constraints, resource constraints, remote work acceptance, and mental health affect remote work effectiveness. The border theory conflict model is empirically validated, and mental health mediates challenges. This nuanced view of remote work distinguishes the research and informs organizational strategies in an evolving workplace. This study collected data from a questionnaire and relevant internet and journal sources. The quantitative descriptive study used cross-sectional data to examine correlations. The sample in this study was 113 respondents, who were then analyzed using the SEM-PLS approach. Role conflict negatively impacts remote work effectiveness, supporting the border theory conflict model. Resource constraints negatively correlated with remote work effectiveness. Acceptance of remote work improved effectiveness, but mental health did not. Mental health mediated the negative effects of role conflict, environmental constraints, and resource limitations on remote work effectiveness. The study indicates that role conflict and resource constraints diminish remote work effectiveness, whereas acceptance enhances it. Organizations should address role conflicts and provide sufficient technological resources, fostering a positive attitude toward remote work and prioritizing employee mental health for improved outcomes. Keywords: Constraints; Mental Health; Post-Covid-19; Remote Work; Role Conflict